E-PJJ students’ attitudes towards E-learning in UiTM Melaka and the factors that influence it / Muhammad Ikhwan Syafiq Zulkifli - Zulkifli, Muhammad Ikhwan Syafiq (2011)
This study investigated the UiTM Malacca e-pjj students’ attitude towards e-learning and the factors that influence it. Specifically, it examined the demographic and other factors, which are age, gender, length of exposure to e-learning and computer literacy. The research design was a quantitative Non-experimental research designs that used the attitude towards elearning questionnaires and the factors that influence it that was adapted from Cheng (2006) and Jenkins (2008). The independent variables were the age group, gender, length of exposure and computer literacy while the dependent variable is attitude towards e-learning. Data obtained from the questionnaire were analyzed using descriptive statistics, One-way ANOVA, Independent Sample t-test, Chi square, Pearson’s product Moment Correlation Coefficient. The findings of the study revealed that age, gender and length of exposure do not have any significance towards the students’ attitude in e-learning. Computer literacy is the only variable that showed significance and has strong relationship. Further analysis was done to check whether age, gender or length of exposure has any significance towards computer literacy. It was found that only gender has significant relationship with male students having higher level of computer literacy compared to female students. Pedagogical implications are offered along with suggestions for further research.